Composites of HKUST-1@nanocellulose for gas-separation and dye-sorption applications - Muhamed, Shamna; Sunny, Blesson; Kunjattu, Shebeeb H.; Alagarsamy, Thirumurugan (CHEMISTRY-A EUROPEAN JOURNAL, 2023)
In this study, composites of HKUST-1 MOF with nanocellulose, HKUST-1@NCs, have been prepared and explored for CO2/N-2 gas-separation and dye-sorption based applications. Our biopolymer-MOF composites are prepared via a copper ion pre-seeding method, in which, the HKUST-1 crystallites are grown in situ on the Cu-seeded and carboxylate anchored NC fibers for a better interfacial integration between the MOF and the polymer matrices. Static gas sorption studies show the capability of one of our HKUST-1@NC composites to reach similar to 300 % enhancement in the CO2/N-2 sorption selectivity compared to the corresponding MOF alone - blank reference sample prepared at similar conditions. The same composite, C100, in the bulk powder form, shows a remarkable IAST sorption selectivity of 298 (CO2/N-2) at 298 K and 1 bar for the CO2/N-2 (15/85, v/v) gas mixture. The relative position of the C100, in the bound plot visualizations of the CO2/N-2 separation trade-off factors indicate a significant potential. The HKUST-1@NC composites have also been processed along with a polymeric cellulose acetate (CA) matrix as HKUST-1@NC@CA films to study them as free-standing mixed-matrix membranes. The CO2/N-2 sorption selectivity, at 298 K and 1 bar is 600 for one such membrane, C-120@CA, as bulk sample studied by the static gas sorption. The composite, C120, exhibits a good uptake with an enhancement of 11 % for alizarin and 70 % for Congo red in comparison to the uptakes of the corresponding blank reference HKUST-1 sample, B120.
Keywords: CO2 separation; dye sorption; MOFs; nanocellulose composites; sustainable polymers